‘Seals’, ‘bitches’, ‘vixens’, and other zoomorphic insults: the animalisation of women as an expression of misogyny in the Spanish Manosphere - Charo Lacalle; Beatriz Gómez-Morales; Mireya Vicent-Ibáñez; Sara Narvaiza (Cogent Arts & Humanities)
The animalisation of women is a recurrent strategy of dehumanisation in Manosphere discourses. Its normalisation as a social phenomenon and its popularity are rooted in short and sententious genres (proverbs, sayings, etc.), which have significantly contributed to reaffirming the status quo of domination largely assigned to men in myths and philosophical theories. This article analyses the use of misogynistic zoomorphism in Burbuja.info, a Spanish economic forum whose extreme neoliberal perspective provides a suitable breeding ground for sexism. The corpus was constructed by identifying the most frequent examples of zoomorphism detected in an initial search of the approximately six million comments posted in the forum between 1 January 2022 and 31 May 2023. The research combines different digital techniques for the construction and quantitative analysis of the corpus with a qualitative analysis of examples of misogynistic zoomorphism. The analysis reveals that, while hostile sexist comments do a systematic comparison of women with the most undesirable traits culturally associated with animals, the positive aspects are never transferred to figurative use. The research also highlights the role played by some rhetorical strategies in the discursive construction of misogyny, such as metaphorical use of humour.